The Status of Literary Monuments in National and International Law - Мартыненко, Игорь (Teisė, 2018)
[full article in Russian; summary in Lithuanian]Libraries play an important role in the formation of personality, patriotism and a sense of national pride, strengthening the country’s authority in the international arena. The public mission of libraries is to collect and keep the national memoryof states, depositaries of treasures of knowledge and to provide access to this information to new generations. Among thetasks solved by libraries, the principles of their activities are to ensure the availability of cultural goods, to promote the protection of historical, cultural and archaeological heritage. The article analyzes the current situation of legislation on the protection of historical and cultural heritage. The author for the first time proposes a new approach in the science of international law: to adopt the UNESCO Convention «On the protection of book monuments».
Keywords: none